Faktor yang Berhubungan dengan Picky Eating pada Anak Usia Prasekolah: Factors Associated with Picky Eating in Preschool Children - Fitria Wahyu Ariyanti; Atikah Fatmawati; Ike Prafita Sari (Universitas Airlangga, 2023)
Background: Picky eating is an eating disorder in children that harms the child or caregivers. Picky eating can cause growth disorders and affect children's nutritional status. Various factors influence picky eating: parents' eating behavior, children's appetite, history of exclusive breastfeeding, MP-ASI, diseases in children, the interaction between parents and children, caregivers, and psychological factors. Objective: This study aimed to analyze the factors associated with picky eating in preschool-aged children in Dusun Terate, Karangsentul Village, Pasuruan. Method: This study uses a correlational research design. The population in this study was 72 parents and was taken by proportionate stratified random sampling of 51 samples. The instruments used were parenting style questionnaires, parental eating behavior questionnaires, and picky eating questionnaires. The statistical analysis used was Spearman's Rank test and Chi-Square. Results: The results showed no relationship between a history of exclusive breastfeeding (p=0.590) and picky eating in preschool-aged children. There is a relationship between parenting style (p<0.001) and parental eating behavior (p=0.006) with picky eating in preschool-aged children. Conclusion: A history of exclusive breastfeeding is not the only factor that causes picky eating in children. Democratic parenting and good parenting behavior do not cause picky eating in children. So it is expected that parents need to apply democratic parenting and apply good eating behavior so that children do not experience picky eating.